Percutaneous Needle Guided Localization of Asynchronous Metastatic Implants: A Novel Approach to Successful Surgical Metastectomy - Mahmood, Ali; Yaakovian, Michael; Shahid, Adeel (British Journal of Healthcare and Medical Research, 2023)
Colon cancer is the second most prevalent cancer in the population. Curative resection is the treatment of choice for stages one and two, however successful operative resection of advanced staged cancers offers the most promise for achieving and sustaining remission. Asynchronous metastatic implants in the abdominal cavity present a difficult challenge for the surgeon. Operative resection of small implants is often met with difficulty of localization. Obscurity in the location of these lesions can lead to incomplete or failed metastectomy or intra-abdominal injury. We present a novel technique where intra-abdominal implants can be marked with a percutaneous approach, minimal anesthesia, low morbidity and optimize curative resection. Working with interventional radiology, the asynchronous small implant was successfully approached percutaneously. Tattoo dye, used in endoscopy, was then injected into the implant. The patient was subsequently taken to the operating room and underwent a successful metastectomy with negative margins. The patient achieved remission.